A novel chitosan–vanadium-titanium-magnetite composite as a superior adsorbent for organic dyes in wastewater. (September 2020) - Zhang, Wei; Lan, Yingying; Ma, Mengting; Chai, Senyou; Zuo, Qiting; Kim, Ki-Hyun; Gao, Yaqian
Highlights: A novel composite CS-VTM was prepared through one-pot synthesis. CS-VTM is an ecofriendly adsorbent for effective removal of dye in wastewater. CS-VTM is demonstrated as the superior adsorbent based on performance evaluation. The adsorption of CR by CS-VTM was attributed to the formation of hydrogen bonds. Abstract: In this research, a novel chitosan (CS)–vanadium-titanium-magnetite (VTM) composite was designed and synthesized. The interaction between CS-VTM and Congo red (CR) dye conformed to a pseudo-second-order model to support the potent involvement of chemisorption. The effects of adsorbent dosage, reaction temperature, and initial solution pH on adsorption of CR were investigated. Approximately 99.1% of CR (100 mg/L) was adsorbed at a CS-VTM dose of 2.0 g/L or above, while such a reaction was favored at temperatures of 65 °C and pH of 6.0. Thermodynamically, the adsorption of CR proceeded spontaneously (ΔG < 0) above 35 °C. According to scanning electron microscopy, X-ray photoelectron spectroscopy, Fourier transform infrared spectrometer, and zeta potential analysis, its adsorption on CS-VTM can be attributed to electrostatic attraction and hydrogen bonds. The prepared CS-VTM exhibited superior adsorption performance on removal of CR as evidenced by significantly large partition coefficient of 108.3 mg g −1 μM −1 (equilibrium adsorption capacity of 62.2 mg/g at CR dose of 100 mg/L). Overall, the CS-VTM proved to be a promising and environmentally friendly adsorbent for the highly efficient and effective removal of organic dyes among the comparable sorbents studied to date.